2021
DOI: 10.1055/a-1522-5178
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Cholestasis of Pregnancy

Abstract: Intrahepatic cholestasis of pregnancy (ICP) is a rare but potentially serious complication of pregnancy, the main symptom of which is intense pruritus with elevated serum levels of bile acids. The elevated serum bile acid concentration is regarded as a predictor for poor perinatal outcome including intrauterine death. Ursodeoxycholic acid (UDCA) has become established as the treatment of choice in clinical management to achieve a significant improvement in symptoms and reduce the cholestasis. Pregnant women wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
4
0
2
Order By: Relevance
“…Our study also found that twin pregnancies and IVF were associated with a higher risk of ICP, which is consistent with previously reported findings [ 26 , 27 , 39 ]. The association of ICP with twin pregnancies and IVF may be related to the increased levels of hormones in this population, which triggers the accumulation of progesterone metabolites, resulting in disordered hepatocyte bile acid secretion and cholestasis [ 4 , 14 , 26 , 40 ]. Moreover, studies have reported that a higher level of oestrogen in twin pregnancies is correlated with an increased risk of ICP [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also found that twin pregnancies and IVF were associated with a higher risk of ICP, which is consistent with previously reported findings [ 26 , 27 , 39 ]. The association of ICP with twin pregnancies and IVF may be related to the increased levels of hormones in this population, which triggers the accumulation of progesterone metabolites, resulting in disordered hepatocyte bile acid secretion and cholestasis [ 4 , 14 , 26 , 40 ]. Moreover, studies have reported that a higher level of oestrogen in twin pregnancies is correlated with an increased risk of ICP [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ICP may cause preterm birth, foetal asphyxia, meconium-stained amniotic fluid, cardiotocography abnormalities, a low (<7) 5-min Apgar score, respiratory distress syndrome, and even intrauterine foetal death [ 5 , 10–13 ]. The pathogenesis of ICP is multifactorial and remains unclear although hormonal, genetic, and environmental factors have been implicated [ 4 , 14–16 ]. Previous studies have shown that multiple pregnancies, in vitro fertilization (IVF), maternal age >35 years, women with a history of liver-related diseases, particularly gallstone and chronic hepatitis C infection, as well as a previous history of ICP increase the risk [ 8 , 17–21 ].…”
Section: Introductionmentioning
confidence: 99%
“…biliares dependientes de sodio y del receptor 4 del factor de crecimiento de fibroblastos de membrana (19,20). También existe la posibilidad de utilizar s-adenosilmetionina junto con UDCA en el tratamiento de la CIE, mediante una acción sinérgica para reducir las concentraciones de ácidos biliares (23,24).…”
Section: Complicaciones Maternas Y Perinatalesunclassified
“…Este es administrado por vía oral a dosis de 10-16 mg/Kg/ día, dos o tres veces al día, alcanzando una dosis de 250-300 mg (17,18). La administración de UDCA en embarazadas con CIE y tiempo de protrombina prolongado puede disminuirse en dosis de 10 mg/Kg/ día para minimizar el riesgo de hemorragia posparto, asociada a deficiencia de vitamina K (factores II, VII, IX y X) (19).…”
Section: Manejounclassified
“…The general incidence of IHCP depending on the geographic variation varies from 1.0-27.6%. 5,6 It shows differences based on environmental factors and ethnic groups. , Incidence is 1.24% in the Indian population, while it is 1.46% in the Pakistani population, the white population has a low incidence of 0.62%.…”
Section: Introductionmentioning
confidence: 99%